Age-related changes in processing auditory stimuli during visual attention: evidence for deficits in inhibitory control and sensory memory - Alain, C; Woods, D L (Psychology and aging, 1999)
Age-related declines in attention and cognition have been associated with a difficulty in inhibiting the processing of task-irrelevant information (i.e., the inhibitory deficit hypothesis). However, evidence supporting the inhibitory deficit hypothesis remains equivocal, in part because of complexities in examining the processing of irrelevant stimuli using purely behavioral techniques. The effects of age on the processing of task-irrelevant stimuli were examined using scalp-recorded event-related brain potentials. Participants performed a visual discrimination task while standard and deviant auditory stimuli were presented in the background. Deviant auditory stimuli generated a mismatch negativity (MMN) wave that decreased with age, in part because of an age-related enhancement in sensory-evoked responses. The age-related changes in processing task-irrelevant auditory stimuli are consistent with the inhibitory deficit hypothesis and suggest that impaired inhibitory control of sensory input may play a role in the age-related declines in performance during selective attention tasks.